Encapsulation of cochleates derived from salmonella infantis with biopolymers to develop a potential oral poultry vaccine - Avendaño, Constanza; Vidal, Sonia; Villamizar Sarmiento, María Gabriela.; Guzmán, Miguel; Hidalgo, Héctor; Lapierre, Lisette; Valenzuela, Carolina; Sáenz, Leonardo (MDPI, 2021)
The aim of this study was to develop and characterize Salmonella enterica serovar Infantis (S. Infantis) cochleates protected by encapsulation technology as a potential vaccine and to determine its safety in pullets. Cochleates were encapsulated by two technologies, spray drying and ionotropic gelation at different concentrations (0–15% v/v), and were characterized by physicochemical proper- ties, protein content and Fourier Transform Infrared Spectroscopy (FTIR). The cochleates were white liquid suspensions with tubular shapes and a protein content of 1.0–2.1 mg/mL. After encapsulation by spray drying, microparticles ranged in size from 10.4–16.9 μm, were spherical in shape, and the protein content was 0.7–1.8 mg/g. After encapsulation by ionotropic gelation, beads ranged in size from 1620–1950 μm and were spherical in shape with a protein content of 1.0–2.5 mg/g. FTIR analysis indicated that both encapsulation processes were efficient. The cochleates encapsulated by ionotropic gelation were then tested for safety in pullets. No ill effect on the health of animals was observed upon physical or postmortem examination. In conclusion, this study was the first step in developing a potential oral S. Infantis vaccine safe for poultry using a novel cochleate encapsulation technology. Future studies are needed to determine the effectiveness of the vaccine.
Keywords: Cochleate.; Encapsulation.; Vaccine.; Poultry.; Salmonella Infantis.